China's strategic interests in the South China Sea power and resources - Burgos Caceres, Sigfrido (London New York Routledge/Taylor & Francis Group, 2014)
"Explores China's strategic interests in the South China Sea, with a specific emphasis on power projection and resource security. Contains sections on China's power and resources and case studies on Japan, Vietnam, the USA and the Philippines, and discusses how China's actions are reshaping the power dynamics in East and South-East Asia"-- Provided by publisher.
Assessing China's external and internal dynamics and influences -- Understanding China's global search for energy and resources -- China's oil security : diplomacy, economics and the prospects for peaceful growth -- Japan -- Philippines -- USA -- Vietnam -- Power projection -- Resource security.
Includes bibliographical references (pages 143-154) and index.
Keywords: National security -- China; Sea-power -- China; Natural resources -- South China Sea; Energy security -- China; Natural resources -- China; China -- Strategic aspects; South China Sea -- Strategic aspects; China -- Foreign relations -- 21st century